Efektivitas Stretching terhadap Pekerja Kantoran yang Mengalami Nyeri Low Back Pain - Andari Elsa Dwi Putri; Masfuri Masfuri; Prima Agustia Nova (Journal of Telenursing (JOTING), 2023)
The aim of this literature review is to obtain an overview regarding the effectiveness of stretching, such as reducing complaints of low back pain, relaxing muscles, preventing spasms, and preventing musculoskeletal disorders due to work risks and increasing the knowledge of office workers with exercises that can provide comfort. The method used in this journal analysis is a literature review resulting from the identification of several journals. The results of the research show that stretching is a relaxation activity for the muscles that can increase muscle flexibility and mobility and can maximize the range of motion of the joints. Stretching is done routinely 2-3 times every week with 15-30 second movements and repeated 2-3 times. time. In conclusion, stretching is an exercise that has been proven to have a significant effect on reducing low back pain. Apart from that, stretching can also relax the muscles while working, so that office workers can feel comfortable while working. Keywords: Low Back Pain, Pain, Office Workers, Stretching